Biography: A Very Short Introduction - Lee, Hermione (New York Oxford University Press, 2009)
Hermione Lee is one of the leading literary biographers in the English-speaking world, the author of widely acclaimed lives of Edith Wharton and Virginia Woolf. Now, in this Very Short Introduction, Lee provides a magnificent look at the genre in which she is an undisputed master--the art of biography. Here Lee considers the cultural and historical background of different types of biographies, looks at the factors that affect biographers, and asks whether there are different strategies, ethics, and principles required for writing about one person compared to another. She also discusses contemporary biographical publications and considers what kind of "lives" are the most popular and in demand. And along the way, she answers such questions as why do certain people and historical events arouse so much interest? How can biographies be compared with history and works of fiction? Does a biography need to be true? Is it acceptable to omit or conceal things? Does the biographer need to personally know the subject? Must a biographer be subjective?
Includes Index and Illustrations.
Keywords: Biography as a literary form